(untitled) (TAJ: Journal of Teachers Association, 2019)
This study was carried out in the Department of Medicine, Rajshahi Medical College, in 2006-2007 to study the thyroid peroxidase (TPO) antibody level among hypothyroid patients and to find out the effects of L-thyroxine therapy in TPO-antibody titer. After thorough physical examination and relevant investigations, 100 patients of hypothyroidism were enrolled in this study. The selected patients were given L-thyroxine replacement therapy at a dose of 50-150 microgram/d. Before starting L-thyroxine, serum was collected from all patients to estimate anti TPO-antibody level. All patients were followed-up after 12-28 weeks of full dose of L-thyroxine therapy. Patients with high TPO-Abs at baseline, only 17.6% turned into euthyroid (based on composite clinical score), whereas about 42% of the patients who did not have high TPO-Abs became euthyroid suggesting that patients with high TPO Abs may show significantly poor response to treatment compared to the patients without high TPO Abs (p < 0.001). Patients with high TPO-Ab titers also showed a decreased biochemical response (TSH values) compared to the patients without high TPO-Ab positive patients. So, TPO-Ab plays a significant role in causation of the disease and is also associated with poor treatment response with L-thyroxine replacement therapy. TAJ 2018; 31(2): 45-49